Anti-Markovnikov hydrofunctionalization of alkenes : use of a benzyl group as a traceless redox-active hydrogen donor - Lonca, Geoffroy Hervé (2022)
A protocol for the anti-Markovnikov hydrofunctionalization of alkenes has been developed by the use of a benzyl group as a traceless redox-active hydrogen donor. Under copper catalysis and in the presence of CF3 - or N3 -containing hypervalent iodine reagents, a series of homoallylic alcohol derivatives were hydrofunctionalized regioselectivity. A similar principle was also applied to the hydrofunctionalization of alkenols.